Safety and Efficacy of Human Chorionic Gonadotropin Hormone-Derivative EA-230 in Cardiac Surgery Patients: A Randomized Double-Blind Placebo-Controlled Study. Issue 5 (15th April 2021) - van Groenendael, Roger; Beunders, Remi; Hemelaar, Pleun; Hofland, Jan; Morshuis, Wim J.; van der Hoeven, Johannes G.; Gerretsen, Jelle; Wensvoort, Gert; Kooistra, Emma J.; Claassen, Wout J.; Waanders, Denise; Lamberts, Maud G. A.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: To determine the safety and efficacy of human chorionic gonadotropin hormone-derivative EA-230 in cardiac surgery patients. Cardiac surgery induces systemic inflammation and may impair renal function, affecting patient outcome. EA-230 exerted immunomodulatory and renoprotective effects in preclinical models and was safe and showed efficacy in phase I and II human studies. DESIGN: Double-blinded, placebo-controlled, randomized study. SETTING: Collaboration of the Cardiothoracic Surgery, Anesthesiology, and the Intensive Care departments of a tertiary hospital in the Netherlands. PATIENTS: One hundred eighty patients undergoing an on-pump coronary artery bypass procedure with or without concomitant valve surgery. INTERVENTIONS: Ninety mg/kg/hr EA-230 or placebo administered during surgery. MEASUREMENTS AND MAIN RESULTS: During the study, no safety concerns emerged. EA-230 did not modulate interleukin-6 plasma concentrations (area under the curve 2, 730 pg/mL × hr [1, 968–3, 760] vs 2, 680 pg/mL × hr [2, 090–3, 570] for EA-230 and placebo group, respectively; p = 0.80). Glomerular filtration rate increased following surgery (mean ± sem increase in the EA-230 vs placebo groups: glomerular filtration rateiohexol measured using iohexol plasma clearance: 19 ± 2 vs 16 ± 2 mL/min/1.73 m 2 ; p = 0.13 and estimated glomerular filtration rate with the Modification of Diet in Renal Disease equation using creatinine: 6 ± 1 vs 2 ± 1 mL/min/1.73 m 2 ; p = 0.01). The "injury" stage of the Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease criteria for acute kidney injury was 7% in the EA-230 group versus 18% in the placebo group ( p = 0.07). In addition, EA-230-treated patients had a less positive fluid balance compared with placebo-treated patients (217 ± 108 vs 605 ± 103 mL; p = 0.01), while the use of vasoactive agents was similar in both groups ( p = 0.39). Finally, hospital length of stay was shorter in EA-230 treated patients (8 d [7–11] vs 10 d [8–12]; p = 0.001). Efficacy results were more pronounced in patients that had longer duration of surgery and thus longer duration of study drug infusion. CONCLUSIONS: EA-230 was safe in patients undergoing on-pump cardiac surgery. It did not modulate interleukin-6 plasma concentrations but appeared to exert beneficial renal and cardiovascular effects and shortened in-hospital length of stay.